Chlorine dioxide intake for COVID-19 - Gonzales, Gustavo F. (2021)
For many years, chlorine dioxide has been used for its main characteristic as a disinfectant, covering various areas of application such as sanitary, food, industrial, etc.The evidence reported to date cites various studies in animal models, from reviews on toxicokinetics to the application or uses of the compound. Its power as a bactericide, virucidal and microbiological eliminator made it a source of water control and purification.The controversy currently generated is about the use of this compound for the treatment and control of COVID-19.There has been evidence of inconsistency with some reported results and that its application in SARS-CoV-2 positive patients or to prevent COVID-19 may have adverse effects, such as an increased number of poisonings and, in other cases, death. In the present review it is detailed, from the scientific evidence reported, the effects of this compound on health and the interaction with SARS-Cov-2 virus.